Governor Phillip and the early settlement of New South Wales - Milford, G. D. (Gerald Douglas) (Sydney : Harbour Newspaper & Pub. Co., 1935)
Includes chapter entitled "The Australian Indians and Phillip" recording Phillip's perceptions and treatment of the Aboriginal people he encountered, including Aranbanoo (Manly), Bennelong, Colbee and Yemmerrawannie.
Includes index.
Bibliography: p. 83.
Keywords: Phillip, Arthur, -- 1738-1814.; Aboriginal Australians -- Treatment; Race relations - Attitudes; Race relations - Representation; Settlement and contacts - Colonisation - 1788-1850.; New South Wales -- History -- 1788-1851.; Norfolk Island; New South Wales (NSW); Warrane / Sydney Cove (NSW SI56-05)